2017
DOI: 10.1515/tjeb-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foreign Direct Investment on the Romanian Labour Market: New Evidence from a Pooled Model

Abstract: The present paper presents a series of results concerning the labour market impact of the foreign direct investment (FDI) ("crawling" effect).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Mah took South Korea as the research object and concluded that FDI would bring more serious income inequality to South Korea [29]. Diaconu et al also found evidence from Romania's domestic labor market that FDI will widen the income gap of employees in different industries [30]. This research shows that FDI inflow has the potential to have a 'widening income gap' effect on Romania's domestic labor market.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Mah took South Korea as the research object and concluded that FDI would bring more serious income inequality to South Korea [29]. Diaconu et al also found evidence from Romania's domestic labor market that FDI will widen the income gap of employees in different industries [30]. This research shows that FDI inflow has the potential to have a 'widening income gap' effect on Romania's domestic labor market.…”
Section: Literature Reviewmentioning
confidence: 81%